OPTIMASI PERENCANAAN PRODUKSI PADA UMKM KALILA ULTIMATE BANTAL MENGGUNAKAN METODE SIMPLEKS, ANALISIS SENSITIVITAS DAN GOAL PROGRAMMING - Priskila Christine Rahayu; Verel Salomo Ulyano Simatupang; Kezia Tiatira Subagio; Reiner Emmanuel Anggriawan; Sifra Clara Pradiza; Giga Rizkika Caesar (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Kalila Ultimate Bantal, a micro, small, and medium enterprise (MSME), faces challenges in balancing production capacity, sales targets, and operational efficiency. This Community Service Program (PkM) aimed to support production planning through the application of the Simplex Method, Sensitivity Analysis, and Goal Programming. Data were collected through observation and interviews regarding production costs, capacity, and sales targets. The Simplex Method identified the minimum-cost production plan, while Sensitivity Analysis evaluated the robustness of the solution. Goal Programming was then applied to accommodate multiple operational objectives simultaneously. The Simplex Method recommended producing 13 pillows for online sales and 400 pillows for offline sales, resulting in a minimum production cost of IDR 7,802,650 per day. Sensitivity Analysis indicated that the solution remained stable under moderate parameter changes. Goal Programming produced a compromise solution of 13 bolsters for online sales and 348 bolsters for offline sales to satisfy cost, capacity, sales, and profit targets. These findings demonstrate the usefulness of quantitative optimization in supporting MSME production planning and decision-making.